Prediction of the turning and zig-zag maneuvering performance of a surface combatant with URANS - Duman, Suleyman; Bal, Sakir (TECHNO-PRESS, 2017)
The main objective of this study is to investigate the turning and zig-zag maneuvering performance of the well-known naval surface combatant DTMB (David Taylor Model Basin) 5415 hull with URANS (Unsteady Reynolds-averaged Navier-Stokes) method. Numerical simulations of static drift tests have been performed by a commercial RANS solver based on a fmite volume method (FVM) in an unsteady manner. The fluid flow is considered as 3-D, incompressible and fully turbulent. Hydrodynamic analyses have been carried out for a fixed Froude number 0.28. During the analyses, the free surface effects have been taken into account using VOF (Volume of Fluid) method and the hull is considered as fixed. First, the code has been validated with the available experimental data in literature. After validation, static drift, static rudder and drift and rudder tests have been simulated. The forces and moments acting on the hull have been computed with URANS approach. Numerical results have been applied to determine the hydrodynamic maneuvering coefficients, such as, velocity terms and rudder terms. The acceleration, angular velocity and cross-coupled terms have been taken from the available experimental data. A computer program has been developed to apply a fast maneuvering simulation technique. Abkowitz's non-linear mathematical model has been used to calculate the forces and moment acting on the hull during the maneuvering motion. Euler method on the other hand has been applied to solve the simultaneous differential equations. Turning and zig-zag maneuvering simulations have been carried out and the maneuvering characteristics have been determined and the numerical simulation results have been compared with the available data in literature. In addition, viscous effects have been investigated using Eulerian approach for several static drift cases.
Keywords: ship maneuvering; turning circle; zig-zag maneuver; CFD (Computational Fluid Dynamics); DTMB 5415; drift; wave deformations; hydrodynamic derivatives; viscous effects; COMPUTATIONAL FLUID-DYNAMICS; CFD SIMULATIONS; VALIDATION; VERIFICATION; FLOWS; TESTS; 2-D; Engineering